Anti-BCMA CAR-T Cell Therapy in Relapsed/Refractory Multiple Myeloma Patients With Extramedullary Disease: A Single Center Analysis of Two Clinical Trials - Que, Yimei; Xu, Menglei; Xu, Yanjie; Almeida, Varlene Daniela Fernandes; Zhu, Li; Wang, Zhiqiong; Wang, Ying; Liu, Xian; Jiang, Lijun; Wang, Di; Li, Chunrui; Zhou, Jianfeng (Frontiers in Immunology, 2021)
Background The prognosis of relapsed/refractory multiple myeloma (RRMM) patients with the extramedullary disease was significantly poor. Extramedullary multiple myeloma (EMM) patients gained limited benefits from traditional drugs. Anti-B cell maturation antigen (BCMA) chimeric antigen receptor (CAR) T-cell therapy seems to be a promising approach to treat RRMM patients. However, very few clinical studies are designed for EMM. Our study aimed to compare and assess the safety, efficacy, and pharmacokinetics of anti-BCMA CAR-T cell therapy in EMM and non-EMM. Methods The results from published anti-BCMA CAR-T clinical trials, in which raw data of EMM patients were available, were reviewed and summarized. Two trials conducted in our clinical centers were analyzed and presented with detailed data. Results According to published anti-BCMA CAR-T clinical trials, the ORR of EMM ranged from 57% to 100%, with the complete remission (CR) rate of 29% to 60%. Between February 22, 2017, and September 26, 2019, a total of 61 subjects (EMM 25; non-EMM 36) received anti-BCMA CAR-T cell infusion. The data-cutoff date was April 1, 2021. There were no statistical differences between EMM and non-EMM groups in adverse events (AEs), including cytokine release syndrome (CRS). The most common AEs of grade ≥ 3 in both groups were hematologic toxicities. There was no significant difference in the objective response rate (ORR) and ≥ complete remission (CR) rate between both groups. However, the ≥ CR rate of the EMM group was lower than the non-EMM group receiving the fully human anti-BCMA CAR-T cell therapy (p = 0.026). The median progression-free survival (PFS) for EMM and the non-EMM group was 121 days and 361 days, respectively (p = 0.001). The median overall survival (OS) for EMM and the non-EMM group was 248 days and 1024 days, respectively (p = 0.005). The Cmax and AUC0-28d for EMM group were lower than non-EMM group (Cmax, p = 0.016; AUC0-28d, p = 0.016). Extramedullary disease was an independent prognostic risk factor for PFS (hazard ratio, 2.576; 95% CI, 1.343 to 4.941; p = 0.004) and OS (hazard ratio, 2.312; 95% CI, 1.165 to 4.592; p = 0.017) in RRMM patients receiving anti-BCMA CAR-T cell therapy. Conclusions Based on our results, EMM patients could benefit from the two anti-BCMA CAR products, although they had a shorter PFS and OS compared with non-EMM patients. Clinical Trial Registration http://www.chictr.org.cn, identifier ChiCTR-OPC-16009113 and ChiCTR1800018137.